Race to Finding COVID-19 Cure: Could Traditional Herbal Medicine Hold the “Silver Bullet”? An Appraisal of Research Evidence - Adeneye, Adejuwon (Al-Nahrain Journal of Science, 2020)
Background: The global index case of the ongoing novel 2019-nCoV infection was recorded in China in December 2019 and the infection is currently considered global public health and security threat due to its high infectivity, associated high mortality and morbidity, fast replication and mutations and lack of clinically approved drugs and vaccines for its treatment. These have since spurred global race for the discovery and development of effective and safe chemotherapeutic and chemoprophylactic agent(s) for its treatment. In order to harness the potentials and bring to the attention of stakeholders in the healthcare industry anti-COVID-19 potentials inherent in plant-derived bioactive compounds, the present study is designed to rapidly review published basic and clinical studies on traditional medicinal plants with proven anti-COVID-19 natural compounds is undertaken.Methods: Eight online database search engines using some COVID-19 keywords were used to search for literature from between 1 December 2019 and 15 May 2020. Of 218 hits retrieved, only 19 peer-reviewed and published works fulfilled the set criteria and reviewed.Results: Using network pharmacology screening and molecular docking technology, natural bioactive compounds, quercetin, kaempferol, and luteoline were the most prevalent and effective bioactive compounds that directly inhibited SARS-CoV-2 protease and down-regulated inflammation. Also the few clinical studies reviewed showed that COVID-19 positive patients managed with traditional herbal remedies either alone or in combination with conventional antiviral regimen and palliative treatment experienced significant clinical improvements.Conclusions: Overall, these studies provided new evidence to support the possible therapeutic role traditional herbal medicine could offer in the clinical management and prevention of COVID-19. However, more robust and multicenter human trials are still required to verify the efficacy and safety of these remedies.